Development and implementation of near-infrared ultrafast laser sources generated by nonlinear fiber propagation - Domingue, Scott R., author; Bartels, Randy, advisor; Krummel, Amber, committee member; Krapf, Diego, committee member; Marconi, Mario, committee member (Colorado State University. Libraries, 2015)
This dissertation is broken up into three parts: (I) generating high-quality ultrafast pulses around 1060 nm, (II) using the pulses from part (I) to generate pulses around 1300 nm, and (III) analyzing newly developed experimental theories and methods utilizing these pulses for linear and nonlinear microscopy. The majority of the work in this dissertation is choreographing the dance between nonlinear spectral broadening in optical fiber and the associated complexity in accumulated spectral phase. We have developed and employed several systems which manage to accomplish this task quite elegantly due to our technological contributions, producing high-quality pulses with high oscillator-type pulse energies both at 1060 and 1250 nm. In addition to developing some theory and techniques extending current types of nonlinear microscopy, we have as a capstone an experimental microscope cascading several of our primary source and application technologies to conduct an entirely new form of spectroscopic absorption imaging.
Keywords: fiber optics; multiphoton microscopy; nonlinear optics; supercontinuum generation; ultrafast optics